Institutions, innovation, and industrialization : essays in economic history and development - Greif, Avner, 1955-; Kiesling, Laura Lynne, 1965-; Nye, John V. C. (Princeton : Princeton University Press, 2015)
This book brings together a group of leading economic historians to examine how institutions, innovation, and industrialization have determined the development of nations. Presented in honor of Joel Mokyr--arguably the preeminent economic historian of his generation--these wide-ranging essays address a host of core economic questions. What are the origins of markets? How do governments shape our economic fortunes? What role has entrepreneurship played in the rise and success of capitalism? Tackling these and other issues, the book looks at coercion and exchange in the markets of twelfth-century China, sovereign debt in the age of Philip II of Spain, the regulation of child labor in nineteenth-century Europe, meat provisioning in pre-Civil War New York, aircraft manufacturing before World War I, and more. The book also features an essay that surveys Mokyr's important contributions to the field of economic history, and an essay by Mokyr himself on the origins of the Industrial Revolution. -- Provided by publisher.
Introduction : The enlightened economist / Avner Greif, Lynne Kiesling, and John V.C. Nye ; Neither feast nor famine : England before the Industrial Revolution / Cormac Ó Gráda ; Progress, useful knowledge, and the origins of the Industrial Revolution / Joel Mokyr ; Coercion and exchange : how did markets evolve? / Avner Grief ; Meat consumption in nineteenth-century New York : Quantity, distribution, and quality, or notes on the "antebellum puzzle" / Gergely Baics ; Funding empire : Risk, diversification, and the underwriting of early modern sovereign loans / Mauricio Drelichman and Hans-Joachim Voth ; Establishing a new order : The growth of the state and the decline of witch trials in France / Noel D. Johnson, Mark Koyama, and John V.C. Nye -- II. Innovation. Increasing market concentration in British banking, 1885 to 1925 / Fabio Braggion, Narly R.D. Dwarkasing, and Lyndon Moore ; The catapult of riches : The airplane as a creative macroinvention / Peter B. Meyer ; England's eighteenth-century demand for high-quality workmanship : Evidence from apprenticeship, 1710-1770 / Karine van der Beek ; A growth agenda for economic history / Rick Szostak -- III. The Industrial Revolution. Amidst poverty and prejudice : Black and Irish Civil War veterans / Hoyt Bleakley, Louis Cain, and Joseph Ferrie ; How Britain lost its competitive edge : Competence in the Second Industrial Revolution / Ralf R. Meisenzahl ; Regulating child labor : The European experience / Carolyn Tuttle and Simone A. Wegge ; Decomposing the wage gap : Within- and between-occupation gender wage gaps at a nineteenth-century textile firm / Joyce Burnette ; The context of English industrialization / Eric Jones.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Economic history; Histoire économique.; BUSINESS & ECONOMICS -- Economic History; Economic history; Wirtschaftswissenschaften; Wirtschaft; Industrie; Ekonomisk historia; Wirtschaftsgeschichte; Entwicklungstheorie; Industrialisierung; Institutionelle Infrastruktur; Innovation; Economics